2011
DOI: 10.4049/jimmunol.1102319
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: CD40–CD40 Ligand Pathway Plays a Critical CD8-Intrinsic and -Extrinsic Role during Rescue of Exhausted CD8 T Cells

Abstract: CD8 exhaustion mediated by inhibitory PD-1-PD-L1 pathway occurs in several chronic infections including toxoplasmosis. While blockade of PD-1-PD-L1 pathway revives this response, the role of co-stimulatory receptors involved in this rescue has not been ascertained in any model of CD8 exhaustion. This is the first report which demonstrates that one such co-stimulatory pathway, CD40-CD40L, plays a critical role during rescue of exhausted CD8 T cells. Blockade of this pathway abrogates the ameliorative effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 13 publications
4
76
0
Order By: Relevance
“…Consistent with our data, it has been reported previously that PD-1 ligation with its ligand inhibits not only the PI3K-Akt pathway but also the MAPK1 pathway in human T cells activated with anti-CD3 mAb [40]. Another study has also shown that blockade of PD-1 and B7-H1 interaction rescues exhausted CD8 T cells via up-regulation of the CD40 -CD40L ligation pathway [41]. Taken together, these results suggest that downstream of PD-1, in T cells and DCs, is regulated by the common signaling pathways; PD-1 induced in DCs, as well as T cells, acts as a negative-feedback mechanism for the maintenance of immune homeostasis.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our data, it has been reported previously that PD-1 ligation with its ligand inhibits not only the PI3K-Akt pathway but also the MAPK1 pathway in human T cells activated with anti-CD3 mAb [40]. Another study has also shown that blockade of PD-1 and B7-H1 interaction rescues exhausted CD8 T cells via up-regulation of the CD40 -CD40L ligation pathway [41]. Taken together, these results suggest that downstream of PD-1, in T cells and DCs, is regulated by the common signaling pathways; PD-1 induced in DCs, as well as T cells, acts as a negative-feedback mechanism for the maintenance of immune homeostasis.…”
Section: Discussionsupporting
confidence: 93%
“…This makes a pathogen-specific study of polyfunctionality and host morbidity and mortality critical for determining whether gain or loss of polyfunctionality is linked to pathogen clearance. In contrast, in the Toxoplasma model, as we have previously demonstrated [13,36] and further reiterated in the current study, loss of polyfunctional CD8 + T cells is strongly associated with PD-1-mediated CD8 + exhaustion and recrudescence of disease. Moreover αPD-L1 treatment not only upregulated polyfunctional CD8 + T-cell response but also prevented parasite reactivation.…”
Section: Discussionsupporting
confidence: 75%
“…4E and F ϩ T cell recruitment can potentially result in unaltered numbers of CD8 ϩ T cells in these recipients. Hence, to definitively address if control of parasite reactivation had any effect on in situ proliferation, CD8 ϩ T cells were assessed for Ki-67, a widely used maker for cell proliferation (16,17). As shown in Fig.…”
Section: Cd8 ؉ T Cells From Immune Donors Fail To Rescue the Endogenomentioning
confidence: 99%
“…Nevertheless, as our data clearly demonstrate, immunotherapy with immune CD8 ϩ T cells is not an appropriate solution for the rescue of dysfunctional CD8 ϩ T cells. Recent studies from our group have demonstrated that anti-PD-L1 treatment of chronically infected mice augments the levels of CD8 ϩ T cell-expressed Eomes (16,17), a T-box family transcription factor critical for memory development (50). Taking this into consideration, it will be interesting to determine if adoptive transfer of retrovirally transfected Eomes overexpressing CD8 ϩ T cells is able to elicit a more robust and long-lasting outcome.…”
Section: Cd8mentioning
confidence: 99%
See 1 more Smart Citation